Novel treatment modalities for pelvic inflammatory disease using immunomodulating therapy - Yu.E. Dobrokhotova; P.A. Shadrova (LCC «Medicine-Inform», 2021)
Yu.E. Dobrokhotova, P.A. Shadrova Pirogov Russian National Research Medical University, Moscow, Russian Federation Pelvic inflammatory disease (PID) is a significant issue of public health due to its devastating effects on female reproductive health and fertility. Despite extensive development of medicine and the emergence of novel groups of antibacterial agents, the risks of antibacterial resistance rapidly grow, thus requiring complex treatment of infectious inflammatory disorders caused by bacterial flora. The modulation of immune response is the heart of recently developed treatment modalities for various diseases (infections, oncology etc.). A detailed understanding of molecular immunology contributes to the rational development of novel types of immunotherapy, which can be successfully introduced into clinical practice. Numerous findings demonstrate the efficacy of inosine pranobex for various diseases, in particular, in immunocompromised patients. This medication has proven itself due to good tolerability and the lack of serious side effects. Inosine pranobex being a  safe drug that can be used in many treatment schedules, including complex treatment for chronic PID with antibacterial agents. Keywords: inosine pranobex, pelvic inflammatory disease, salpingo-oophoritis, infertility, immunotherapy, sexually transmitted infections, bacterial vaginosis. For citation: Dobrokhotova Yu.E., Shadrova P.A. Novel treatment modalities for pelvic inflammatory disease using immunomodulating therapy. Russian Journal of Woman and Child Health. 2021;4(2):149-154. DOI: 10.32364/2618-8430-2021-4-2-149-154.